A brief descriptive outline of the rules of mixed martial arts and concussion in mixed martial arts - Hamdan, J. L.; Rath, M.; Sayoc, J.; Park, J. Y. (Journal of Exercise Rehabilitation, 2022)
Mixed martial arts (MMA), a combat sport consisting of wrestling, boxing, and martial arts, is a popular activity associated with danger and violence. Of concern are the repetitive head impacts, both subconcussive and concussive, sustained by MMA athletes. The rules of MMA encourage head strikes, but there was no formal concussion protocol in the Ultimate Fighting Championship (UFC) until 2021. Because the UFC was established less than 30 years, the long-term consequences of these repetitive concussive head blows are lacking. In this review, we focus on current literature sought to summarize the current knowledge of repetitive head impacts and concussions in MMA. The objectives were to outline (a) the rules of MMA; (b) the postconcussion protocol for UFC athletes; (c) current behavioral and biochemical diagnostic measures; (d) epidemiology and prevalence of concussion in MMA; (e) long-term effects of subconcussive repetitive head impacts; (f) biomechanics of head impacts; and (g) considerations and research topics that warrant future research.